Christian College Students and Emerging Adulthood: Exploring or Lost?. Issue 2 (November 2016) - Bird, Steven
Students in college today are experiencing a life stage—emerging adulthood—that previous generations did not experience. Society has not provided clear social expectations and boundaries on this life stage yet. This has led to two different research-based characterizations of the reality students are experiencing: a time of exploration and opportunities (Arnett, 2004) and a time of lostness and struggle (Smith, Christoffersen, Davidson, & Herzog, 2011). This research uses data from 6, 074 students at 22 Christian colleges to determine which of these descriptions better characterizes their experiences of emerging adulthood and what role different kinds of religiosity play in those experiences. Generally, students at Christian colleges find emerging adulthood to be a time of exploration and opportunity, and not a time of being lost and disconnected. Religiosity (measured in seven different ways) consistently is associated with decreased lostness, has no effect on exploration, and is associated with an increased perception of opportunity.